Information technology students’ perspectives on differentiated instruction and its impact on their approaches to learning - Jose, Jiyamole; Mathew, Binu Pathippallil (Intelektual Pustaka Media Utama, 2025)
There have been many studies about the effectiveness of differentiated instruction in promoting student-centered learning. However, most of these studies have focused on primary and secondary education. There is hardly any research about its application and effectiveness in higher education settings. Furthermore, there is a need to identify the factors that influence information technology or information technology (IT) students’ motivation, engagement and attitude towards learning to use appropriate instructional strategies. The current research addresses this gap in the literature by investigating the perspectives of university IT students on differentiated instruction and its impact on their learning attitude. A mixed-methods approach was employed, combining survey questionnaires and semi-structured interviews to examine the effectiveness of various instructional strategies, including scaffolded instruction, peer-assisted learning, collaborative learning, and competitive learning, across different IT courses. The results showed that students had a positive attitude toward differentiated instruction. Respondents reported that the tailored teaching methods helped them better engage with the course material and develop more effective learning strategies. Many students stated that the differentiated approach allowed them to capitalize on their strengths and address their weaknesses in a supportive environment. The findings have implications for educators seeking to promote student-centered learning and improve learning outcomes in IT courses.